Closed loop alarm system development using Arduino and Android / Mohd Salahuddin Md Tamperin - Md Tamperin, Mohd Salahuddin (2017)
This paper presents the design of Closed Loop Alarm System Development Using Arduino and Android with low cost and wireless remote control. General idea of Alarm System shows the quality of human being at home. Security system nowadays become a need for houses or commercial premises and available with many modern features. This Bluetooth-triggered alarm security system comes with intelligent alarming. The system only can be accessed and configured by owner using Bluetooth communication via mobile phone to turn it on or off. In this project. PIR sensor of the system will continuously monitor movement or present of human in the building. The Bluetooth module will sent intruder alert message as microprocessor (Aduino) receive signal from PIR sensor. The Arduino is programmed to wait approximately seven minute before activated the siren.